Genetic alteration and immunohistochemical staining patterns of ovarian high‐grade serous adenocarcinoma with special emphasis on p53 immnnostaining pattern. (28th May 2013) - Lee, Sang Hwa; Kim, Hyunkyung; Kim, Wook Youn; Han, Hye Seung; Lim, So Dug; Kim, Wan Seop; Kim, Sehun; Hwang, Tae Sook
Abstract : We evaluated p53, KRAS, BRAF and CTNNB1 mutation and p53, WT1, p16 and beta‐catenin expression in 31 ovarian high‐grade serous adenocarcinoma. Twenty‐five (80.6%) tumors contained functional mutations of p53 ; three frameshift, four nonsense and 19 missense mutations. None of the tumors showed KRAS, BRAF or CTNNB1 mutation. In all 18 tumors with missense mutations, ≥60% of tumor cells were strongly positive for p53 immunostaining whereas all tumors with frameshift or nonsense mutations were completely negative. Missense mutation was correlated with diffuse and strong imunoreaction and frameshift/nonsense mutation was correlated with completely negative immunoreaction ( P = 0.000). Tumors with wild‐type p53 revealed a wide range of immunostaining patterns. In 27 (87.1%) and 18 (58.1%) tumors, ≥50% of tumor cells were moderate to strongly positive for WT1 and p16, respectively. A considerable intratumoral heterogeneity for p16 expression was present. None of the tumors demonstrated nuclear beta‐catenin expression. p53 mutations appear to be a powerful molecular marker for ovarian high‐grade serous adenocarcinoma. Using p53 with an appropriate interpretation criteria together with WT1, p16 and beta‐catenin, most of the high‐grade serous adenocarcinoma could be distinguished from other ovarian tumors.